2013
DOI: 10.1002/jsfa.6364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon monoxide on quality, nutrients and antioxidant activity of post‐harvest jujube

Abstract: Fumigating jujubes with proper concentration of CO probably is a potential novel method for post-harvest jujube preservation in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…TP and antioxidant capacity in 'Jiancui' jujube, including the ability to scavenge DPPH free radicals or FRAP, dramatically increased after being subjected to the storage condition, afterwards progressively decreasing until the end of the storage (Fig. A–C), similar to the results with 'Dongzao' jujube . Compared with the control, fruit treated with Ca(NO 3 ) 2, Ca(OAc) 2 , or SAEW alone significantly increased DPPH radical scavenging capacity, FRAP, TP, and TF (Fig.…”
Section: Resultssupporting
confidence: 76%
“…TP and antioxidant capacity in 'Jiancui' jujube, including the ability to scavenge DPPH free radicals or FRAP, dramatically increased after being subjected to the storage condition, afterwards progressively decreasing until the end of the storage (Fig. A–C), similar to the results with 'Dongzao' jujube . Compared with the control, fruit treated with Ca(NO 3 ) 2, Ca(OAc) 2 , or SAEW alone significantly increased DPPH radical scavenging capacity, FRAP, TP, and TF (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Strengthening cell wall results in the increase in the activity of antioxidant enzymes, reduces ROS and delays senescence. Furthermore, Zhang and Li (2014) reported that any factor affecting the strength of the cell membrane can control active oxygen metabolism and H2O2 by the activation of antioxidant enzymes (Cat, Sod).…”
Section: Catalase Activity (Cat)mentioning
confidence: 99%
“…Dongzao) fruit is extremely susceptible to fungal attack owing to its high level of sugars and occurrence of softening at ambient temperature storage . To maintain fruit quality and prolong its shelf life, various chemical and physical strategies, including gibberellic acid, nitric oxide, carbon monoxide, calcium chloride (CaCl 2 ) and nano‐packing material (nano‐Ag, nano‐TiO 2 , kaolin and polyethylene) treatments, have been employed in the postharvest storage of jujube fruit . Of all these strategies, calcium treatment is the most available and safest method and plays an important role in extending the shelf life of fruits and vegetables .…”
Section: Introductionmentioning
confidence: 99%